COMPOSITION OF NAZIR AD-DURGHILI “NUZKHAT AL-AZKHAN” AS A PART OF THE SOURSEBOOK “AL-MUKHTAR AL-MASUN MIN A‘LAMI AL-KURUN” - Hanmurzaev, Ismail Ibragimovic (History, Archeology and Ethnography of the Caucasus, 2018)
It is known that Daghestan up to the beginning of the 20th century in the civilization plan was guided more by the Arab East. Daghestan scientists were well familiar with many popular religious and literary works of Arabic-speaking authors. At the same time there are some Daghestan educated alim works published in the Arab countries. Among similar works there is "Nuzkhat al-azkhan fi taradzhim ‘ulama ʼ Dagistan" of Nazir ad-Durgili. Owing to the objective reasons in Soviet period the edition of the ad-Durgili’s work was impossible. His introduction to a scientific use had taken place in 2004 in Germany and in 2012 in Russia. As a result of the researches carried out by the author of the present article, it has become clear that this work written by the Daghestan scientist has been partially published in Saudi Arabia in 1995. Over eleven biographies of the Daghestan scientists became a part of the encyclopedic three-volume edition "al-Mukhtar al-masun min ‘alami al-kurun" ("The chosen data on outstanding people of [various] centuries"), prepared by the Saudi scientist Muhammad ibn Hassan ibn Ukayl Musa. In this work the information of bio-bibliographic character about thousands of outstanding Muslims during all the history of Islam has been collected. The offered article is devoted to the comparative analysis of the biographies of the Daghestan scientists provided in it. Texts of biographies of this edition are verified with the autograph of the manuscript provided in the Moscow edition of this composition ad-Durgili. During the research the author of article comes to a conclusion that this edition is actually the first experience of publication of this work. Besides, it has become clear that in the nineties of the last century the scientist Abdulkhamid Dagistani conducted work on preparation for the edition of the full text of this manuscript in Saudi Arabia